Operative Outcomes Between Fistulotomy and Ligation Of Intersphincteric Fistula Tract for Fistula in Ano (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Fistula in ano is a benign anorectal condition. Fistula can indeed be a challenging surgical condition for both patients and surgeons. It is very difficult to treat due to its high recurrence rate and anal incontinence. Ligation of the Intersphincteric Fistula Tract (LIFT) is a new surgical procedure to improve patient outcomes and reduce recovery time in the treatment of fistula in ano. The aim of the study to evaluate the success rate of LIFT procedure.Materials and methods: This comparative study was carried out in the Department of Surgery of Chittagong Medical College Hospital (CMCH), Chattogram, during the period Nov 2019 to Nov 2020. A total of 40 patients with fistula in ano of both male and female above 18 years were included in this study. The fistulotomy patient was considered as group I and LIFT patient was considered as group II. Statistical analysis was obtained by using softwarelike the Statistical Packages for Social Sciences (SPSS-version 22) on a windows computer.  Results: The mean VAS scoring of pain in group I was 2.5±1.1 and in group IIwas 0.9±1.4 at 6 months follow-up. Wound was healed in 15(75.0%) patientsin group I and 20(100.0%) patientsin group II at 6 months follow-up. The mean VAS scoring of pain, and wound healing differences were statistically significant (p0.05) at 6 months follow-up. Incontinence and persistent symptom/LIFT failure were almost similar (p>0.05) between two groups in all follow-ups.   Conclusion: The LIFT procedure provides the benefits of reducing post-operative pain, faster wound healing with no incidence of incontinence and low failure rate in comparison with Fistulotomy. The LIFT procedure is simple, easy to learn and a good choice for the treatment of Fistula in Ano.JCMCTA 2023 ; 34 (2) : 134-140